Association of kidney stone disease with dietary factors: a review - Konjengbam, Henry; Meitei, Sanjenbam Yaiphaba (Anthropological Review, 2020)
Kidney stone disease is one of the most common urologic disorders worldwide. The incidence of kidney stones disease is increasing all over the world. It is a multifactorial disease accompanied by various factors. The dietary factor is one of the most important risk factors for the formation and recurrence of kidney stone disease. Formation and recurrence of kidney stone disease can be prevented by modifying our day to day dietary habits. Fewer intakes of animal protein, higher intake of fluid, higher intake of fruits, and higher intake of green leafy vegetables, which contain a low amount of oxalate, can prevent the formation of kidney stones and recurrence of kidney stones. From this review, it may be presumed that the higher prevalence rate of kidney stone disease in northeast India may be the dietary factors accompanied by environmental and climatic conditions of the region.